2011
DOI: 10.1002/ejoc.201100486
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Phosphonylated and Thiolated Indenones by Manganese(III)‐Mediated Addition of Phosphorus‐ and Sulfur‐Centered Radicals to 1,3‐Diarylpropynones

Abstract: Phosphorus‐ or sulfur‐centered radicals generated from the reaction of manganese(III) acetate with dialkyl phosphonates or arylthiols undergo selective additions to conjugated alkynes followed by cyclization and rearomatization to afford 2‐phosphonyl‐ or 2‐thioaryl‐substituted indenones in fair to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…Consequently, we investigated the annulation reaction in detail to provide an unprecedented direct route to benzophosphole derivatives. Furthermore, it was found that these radical processes can also be promoted by a Mn III salt10a, 11 as well as Ag I .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we investigated the annulation reaction in detail to provide an unprecedented direct route to benzophosphole derivatives. Furthermore, it was found that these radical processes can also be promoted by a Mn III salt10a, 11 as well as Ag I .…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that P‐centered radicals can be formed in the presence of Mn(OAc) 3 through homolytic PH bond cleavage 10a. Therefore, we employed Mn(OAc) 3 ⋅2 H 2 O (1 mmol) in the place of AgOAc for the reaction of 1 a with 2 a , and 3 aa was formed in 50 % yield (entry 9 in Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…149 They also react with 1,3-diarylpropynones affording phosphonated indenones. 150 The authors also found that phosphinoyl radical [e.g. Ph 2 (O)P . ]…”
Section: Synthesis Of Phosphorylated Coumarinsmentioning
confidence: 99%
“…α,β-Acetylenic ketones are widely used in organic synthesis as starting reagents for the preparation of indenones [1], benzodiazepines [2], chromones [3], frutinones [4], pyrazoles [5], and phosphonylated indenones [6]. Such ketones can be prepared by Sonogashira coupling of terminal alkynes and acyl halides.…”
Section: Introductionmentioning
confidence: 99%